Online e-learning and cognitive disabilities: A systematic review. (March 2019) - Cinquin, Pierre-Antoine; Guitton, Pascal; Sauzéon, Hélène
Abstract: For decades now, as the issue of social progress has come to the fore, the drive to improve access to education has been behind the growth in research into e-learning. The current systematic literature review raised the question of the existence of studies addressing the specific needs of persons with cognitive impairments. Indeed, e-learning is expected to be one of the critical tools for improving access to education and ultimately aiding social inclusion. The systematic literature review was performed through a four-step process including an exhaustive search of scientific literature databases, the selection of studies through exclusion and inclusion criteria, and literature analysis and synthesis. The main results are: 1) a lack of e-learning studies addressing the issue of accessibility for people with cognitive impairments (N = 29) with a purpose dominated by design guidelines rather than effectiveness assessment; 2) a weak inclusion of accessibility standards (N = 5) and 3) a weak inclusion of special education findings (N = 3), with a focus on specific neuropsychological disorders or syndromes (dyslexia, ADHD, etc. ) rather than on impairments of cognitive function (attention, memory, etc. ) as promoted by the International Classification of Functioning (World Health Organization, 2001); 4) the identification of five families of accessibility function (adaptive systems, game elements, accessible content, virtual agents and accessible interfaces or environments) and their dependency with activity-domain of learning. Results are discussed in terms of both design and assessment recommendations, promoting a multi-disciplinary approach combining educational sciences, cognitive sciences and computer science to develop more accessible e-learning systems. Highlights: Accessible online e-learning is an urging need for people with cognitive disabilities. Few e-learning studies addressed the cognitive accessibility. Their underpinning in terms of accessibility standards and special education is weak. Their focus is oriented on specific disorder/disease instead of cognitive function. Accessibility functions are learning activity-specific and few assessed with learners.